2000
DOI: 10.1038/sj.ijo.0801079
|View full text |Cite
|
Sign up to set email alerts
|

Misreporting of total energy intake in older African Americans

Abstract: OBJECTIVES: (1) To examine misreporting of total energy intake in older African-American men and women using the double-labeled water procedure; and (2) to identify signi®cant physiological and demographic determinants of total energy intake misreporting in older African Americans. DESIGN: Cross-sectional study examining gender differences and determinants of misreporting of total energy intake in older African-American men and women. SUBJECTS: Sixty-four, older African-American men (n 28) and women (n 36); 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…Older persons may also under-report energy intake. [67][68][69] In our previous analyses, we showed that including only plausible reports resulted in stronger relationships of both eating patterns and dietary composition with BMI in subjects across all age groups. 22,38,39 Our studies also provided strong evidence that when implausible reporting occurs, whole eating occasions are omitted, and reported portion sizes and energy density of both meals and snacks are lower in the total sample compared to the sample limited to plausible reporters.…”
Section: Discussionmentioning
confidence: 85%
“…Older persons may also under-report energy intake. [67][68][69] In our previous analyses, we showed that including only plausible reports resulted in stronger relationships of both eating patterns and dietary composition with BMI in subjects across all age groups. 22,38,39 Our studies also provided strong evidence that when implausible reporting occurs, whole eating occasions are omitted, and reported portion sizes and energy density of both meals and snacks are lower in the total sample compared to the sample limited to plausible reporters.…”
Section: Discussionmentioning
confidence: 85%
“…The %EI from fat was inversely related to the percentage of EI underestimation among 30 obese men, indicating selective underestimation of fat (8). Selective underesti mation of fat and selective overestimation of protein were also observed in 64 older people (10). These find ings may have a substantial impact on studies of diet and health because misleading conclusions with regard to diet and health may be drawn due to selective mises timation of dietary intake (54).…”
Section: Methodsmentioning
confidence: 89%
“…Not only have several factors which are associated with EI underestimation been indicated (3)(4)(5)(6), but it appears that a person whose EI is underestimated on one occa sion is likely to have an underestimated EI on other occasions (7). Furthermore, underestimation may not be food and nutrient neutral and may distort the actual balance of foods and nutrients (3,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice however, 3 d weighed dietary records are often the assessment tool chosen by investigators for intervention studies, as they are deemed to be less intrusive for subjects (2) and can therefore improve subject recruitment. With the shorter recording period comes the concern whether the three recording days are representative of habitual intake (3) .…”
mentioning
confidence: 99%